Inclusiveness of Pioneer Youth Organizations Around Kayuapu Kulon (POPSIKA) in the Multiversity of the Gondangmanis Bae Kudus Community - Rif'an Maulana; Mas’udi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This study analyzes how the Pioneer Youth Organization Around Kayuapu Kulon (POPSIKA) constructs and sustains inclusivity in the plural Muslim–Christian community of Gondangmanis Village, Bae District, Kudus, Indonesia. Using a qualitative case study design, data were collected through participant observation, semi-structured interviews, and documentation, then analyzed thematically. The findings show that POPSIKA develops inclusivity not through formal interfaith dialogue alone, but through everyday civic practices embedded in local community life. Five mechanisms were identified: youth-based social participation, reciprocal interfaith cooperation, negotiated theological boundaries, humanitarian solidarity, and informal conflict management. Muslim and Christian youth support one another during religious celebrations in civic roles, participate in collective work, provide social assistance across religious identities, and manage sensitive issues through deliberation and trusted local communication. The study introduces the concept of bounded inclusivity to explain how religious communities can expand cooperation while preserving theological commitments. This concept challenges the assumption that inclusivity requires the dissolution of religious boundaries. Instead, the findings demonstrate that respected boundaries can become enabling conditions for sustainable coexistence when supported by trust, reciprocity, and shared responsibility. Theoretically, this study contributes to discussions on religious pluralism, youth participation, and social cohesion by offering a grounded explanation of how interfaith harmony is produced in everyday life. Practically, it highlights the strategic role of grassroots youth organizations in preventing sectarian tension and strengthening community resilience. The study suggests that bounded inclusivity may serve as a contextual model for plural communities facing intolerance, polarization, and fragile interreligious relations.